Effect of Fee Based Income and Inflation Rate on Profitability (ROA) on State-Owned Banks Listed at Indonesia Stock Exchange (IDX) for The 2016 - 2020 Period - Yeremia Krisna Trihardianto; Nenik Diah Hartanti (East Asian Journal of Multidisciplinary Research, 2022)
The purpose of this paper is to determine and analyze the effect of fee-based income and inflation rates on profitability (ROA) of state-owned banks listed on the Indonesia Stock Exchange (BEI) for the period 2016-2020 partially and simultaneously. This study uses a quantitative approach and uses secondary data available on the official website www.idx.co.id. The population in this study are state-owned banking companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sampling technique was using purposive sampling method. There are 4 companies sampled in this study. Data analysis techniques in this study using multiple linear regression analysis, correlation analysis, analysis of the coefficient of determination, hypothesis testing, t test and f test. The results showed that fee-based income and the inflation rate partially had no effect on profitability (ROA) of state-owned banks listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period, fee-based income and inflation rates decreased simultaneously. . has no effect on profitability. (ROA) at State-Owned Banks Listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 Period.